Characterising seedling and adult plant resistance to Puccinia hordei in Hordeum vulgare. (19th March 2014) - Sandhu, K.S.; Singh, D.; Park, R.F.
Abstract A set of 113 genotypes of barley (Hordeum vulgare subsp. vulgare), along with the susceptible control genotype Gus, was tested for response to the barley leaf rust pathogen Puccinia hordei in the greenhouse (as seedlings) and field (as adult plants). The tests revealed that 68 lines carried adult plant resistance (APR), 23 lines carried uncharacterised seedling resistance (USR) and that three lines carried the seedling resistance gene Rph3. Nineteen lines lacked detectable seedling resistance and were also susceptible in the field at adult plant growth stages. The presence of marker bPb‐0837, linked to the APR gene Rph20, in 35 of the 68 lines carrying APR, suggested they carry this gene. The remaining 33 lines, which lacked the Rph20 linked marker, are likely sources of new uncharacterised APR. Pedigree analysis of the 68 lines found to carry APR revealed that 32 were related to cv. Gull and to Hordeum laevigatum; two were related to cv. Bavaria and one related to cvv. Manchuria and Taganrog, suggesting that these genotypes may be the ancestral sources of the APR carried by each.